Whole chloroplast genome sequences contribute to phylogenetic relatedness and cultivar identification in cacao (Theobroma cacao L.) - Izzah, Nur Kholilatul; Park, Hyun Seung; ., Reflinur (Emirates Journal of Food and Agriculture, 2023)
Cacao (Theobroma cacao L.) is considered as economic importance crop playing a major role as source of chocolate industries for production of both chocolate candy and cocoa butter. Despite the advantages of cacao in industrial sector, understanding the global structure of cacao chloroplast genome plays a crucial role in explaining phylogenetic relationships and cultivar identification. This study aimed to perform phylogenetic analysis of cacao genotypes and develop DNA barcode markers using cacao chloroplast sequences. Chloroplast genome sequencing of two cacao genotypes (DR-1 and Sca-12) was conducted by the Illumina Miseq platform. Phylogenetic analysis of 12 cacao genotypes including two genotypes sequenced in this study (DR-1 and Sca-12) and ten genotypes previously sequenced (HQ336404, EET-64, ICS-01, ICS-06, ICS-39, Pentagonum, Sca-6, Stahel, Amelonado, and Criollo-22) showed a clear separation between bulk and fine types. This result demonstrated the usefulness of chloroplast sequences in revealing phylogenetic relatedness. Based on comparative chloroplast genome analysis of two cacao genotypes, DR-1 and Sca-12, three insertion/deletion (InDel) markers named as Theca_indel01, Theca_indel02, and Theca_indel03 which designed from the regions of trnA-UGC-rrn23, trnK-UUU-rps16, and rps16 intron, respectively were successfully developed to reveal barcode system for cacao genetic discrimination. Overall, these findings would provide valuable insight into the chloroplast genome structure of cacao plant, as well as information about the benefits of chloroplast sequences for constructing phylogenetic relationships and developing DNA barcode markers.